2014
DOI: 10.1002/eji.201444903
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐λ‐mediated IL‐12 production in macrophages induces IFN‐γ production in human NK cells

Abstract: With increasing interest in alternative options to interferon-alpha-based treatments, IFN-λ has shown therapeutic promise in a variety of diseases. Although the antiviral activity of IFN-λ has been extensively studied, there is limited knowledge regarding the immunological functions of IFN-λ and how these differ from those of other classes of IFNs.In this study, we investigated the effects of IFN-λ on primary human NK cells, both in a direct and indirect capacity. We demonstrate that in contrast to interferon-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 38 publications
7
47
0
Order By: Relevance
“…A direct effect of IFN-λ on NK cells has been suggested following the failure of transferred IFN-λR1-deficient NK cells in suppressing tumor growth in vivo [82]. However, no direct evidence has been reported in vitro, in accordance with our initial report [78] and other studies, demonstrating that IFN-λ was not directly acting on NK cells [88,89]. Innate immunity may also be mediated by macrophages and neutrophils, and there is one report suggesting IFN-λ may influence innate immunity against a fibrosarcoma tumor model through these cells [76].…”
Section: Development Of Ifn-λ As Antitumor Agent: Preclinical Datasupporting
confidence: 67%
“…A direct effect of IFN-λ on NK cells has been suggested following the failure of transferred IFN-λR1-deficient NK cells in suppressing tumor growth in vivo [82]. However, no direct evidence has been reported in vitro, in accordance with our initial report [78] and other studies, demonstrating that IFN-λ was not directly acting on NK cells [88,89]. Innate immunity may also be mediated by macrophages and neutrophils, and there is one report suggesting IFN-λ may influence innate immunity against a fibrosarcoma tumor model through these cells [76].…”
Section: Development Of Ifn-λ As Antitumor Agent: Preclinical Datasupporting
confidence: 67%
“…Similarly, only some subsets of myeloid immune cells, such as human monocyte-derived macrophages 61 , pDCs [60][61][62] and some dendritic cell subsets in humans and in mice 63 , respond directly to type III IFN. For natural killer (NK) cells, reports have come to opposite conclusions about the ability of type III IFNs to influence IFN-γ secretion by NK cells [64][65][66] . However, adoptive transfer experiments in mice using IFN-λR1-deficient (Ifnlr1 −/− ) NK cells Figure 2 Signaling pathway of type I and type III IFNs.…”
Section: Effects Of Type III Ifn On Immune Cellsmentioning
confidence: 96%
“…Individuals bearing the CC genotype also displayed increased NK cell function measured by IFN-γ production after stimulation irrespective of infectious outcome suggesting that IFN-λ genotype influenced NK cell function but that this was not sufficient to achieve spontaneous HCV clearance (31). Although IFNLR1 mRNA expression could be detected in NK cells (59, 60), they express very low levels of the specific type III IFN receptor (IFN-λR1) on cell surface, even after IFN-α stimulation (31, 61, 62). Treatment of purified NK cells with IFN-λ had no effect on neither NK cytotoxicity nor cytokine production (31, 60, 62, 63).…”
Section: Ifn-λ Interaction With Hematopoietic Cellsmentioning
confidence: 99%
“…Although IFNLR1 mRNA expression could be detected in NK cells (59, 60), they express very low levels of the specific type III IFN receptor (IFN-λR1) on cell surface, even after IFN-α stimulation (31, 61, 62). Treatment of purified NK cells with IFN-λ had no effect on neither NK cytotoxicity nor cytokine production (31, 60, 62, 63). On the other hand, it was reported that the level of expression of IFN-λR1 could be upregulated by IFN-λ treatment (59) and studies in IFN-λR1 −/− mice have demonstrated that this receptor is required for optimal antitumoral in vivo activity of NK cells (64), suggesting that in some activation context, NK cells could become sensitive to type III IFNs.…”
Section: Ifn-λ Interaction With Hematopoietic Cellsmentioning
confidence: 99%
See 1 more Smart Citation